Great leaders equal great schools : alliances and discourse for educational reform - Cyprès, Autumn; Breckner, John (Leaders, schools, and change., 2012)
The networks of Tennessee politicians, school leaders, and academics are rife with significant contributors to the national fabric of educational reform. This cadre includes Former White House Chief of Staff Howard Baker, United States Senator Bill Frist (currently Chairman of the Tennessee State Collaborative on Reforming Education) former United States Secretary of Education Lamar Alexander (currently United States Senator and Conference Chair of the Republican Party) and current Governor Bill Haslam. This network has deep, current ties to The University of Tennessee, the Knoxville area, and school systems across the state of Tennessee. The Center for Educational Leadership is a highly funded, highly visible model for education reform throughout the state of Tennessee. This 3 book series will serve as a calling card for all activities that The Center for Educational Leadership is involved in around the state of Tennessee and the United States. This includes all school leadership summits for policy makers, practitioners, scholars, and legislators. It represents the shared vision and commitment of educational leaders, politicians, educational reformers, and legislators. This book will be distributed to school leaders, professional development coaches, teacher unions, scholars at several Tennessee institutions of higher education, and members of the Tennessee legislature and Department of Education. The audience for this series is primarily school leaders and scholars who are launching and designing new programs or revising and strengthening existing programs. However, those who are discussing policy at the local, state, and national level would be interested in the information given within these pages as it relates clearly to their work in educational leadership.